EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH NOMOR 7 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH DI KABUPATEN KARIMUN, PROVINSI KEPULAUAN RIAU - Rosalinda Rosalinda; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2020)
A clean and healthy living environment is a necessity for all mankind and receives serious attention from all countries including Indonesia. But in reality The condition of garbage disposal in Karimun Regency is very concerning even though the Regional Government of Karimun Regency has issued Regional Regulation Number 7 of 2013 concerning Waste Management. How effective is the Regional Regulation of Karimun Regency Number 7 of 2013 concerning Waste Management in Karimun Regency, Riau Islands Province? This research was conducted by legal research methods for academic purposes.The results of this study, namely the effectiveness of the Karimun Regency Garbage Management Regional Regulation, experienced the highest obstacles in the coaching section, where the Sanitation Office had not succeeded in conducting socialization which then had a sustainable effect, namely the local community was not aware of their rights and obligations when participating in Waste Management in the Karimun Regency area. The central government should carry out a survey to examine the factors that hinder the fulfillment of the Waste Management Regulation. From the survey, it is possible to make improvements to the existing waste management regulations, such as a new socialization mechanism and other provisions such as higher dues.